2020
DOI: 10.1186/s13008-020-00061-6
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP5 increases cell invasion and inhibits cell proliferation by EMT and Akt signaling pathway in Glioblastoma multiforme cells

Abstract: Background: Recurrence of Glioblastoma multiforme (GBM) seems to be the rule despite combination therapies. Cell invasion and cell proliferation are major reasons for recurrence of GBM. And insulin-like growth factor binding protein 5 (IGFBP5) is the most conserved of the IGFBPs and is frequently dysregulated in cancers and metastatic tissues. Results: By studying the human glioma tissues, we find that IGFBP5 expression associate to the histopathological classification and highly expressed in GBM. Using IGFBP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Among them, ARHGAP11A, DRP2, HNRNPA3, KLF10, PAIP1, and RCN1 have not yet been studied in gliomas. Three mRNAs were identified as oncogenes in gliomas, which was consistent with our multivariate Cox regression analysis result: IGFBP5 can increase cell invasion and inhibit cell proliferation via the EMT and Akt signaling pathways in GBM ( Dong et al, 2020 ); IP6K2 was reported to promote cell proliferation and inhibit cell apoptosis under the regulation of the LINC00467/miR-339-3p axis ( Liang & Tang, 2020 ); and KPNA4 is capable of facilitating epithelial-mesenchymal transition in glioma, which can be suppressed by miR-181b, a tumor-suppressive miRNA ( Wang et al, 2015 ). Surprisingly, the roles of the other two mRNAs in glioma were shown to be different from our analysis result: NRP2 promoted glioma cell growth, invasion, and angiogenesis ( Zheng et al, 2013 ); and SEMA5A, whose expression is markedly reduced in higher grades of glioma, can impede motility and promote differentiation of human gliomas ( Li & Lee, 2010 ).…”
Section: Discussionsupporting
confidence: 85%
“…Among them, ARHGAP11A, DRP2, HNRNPA3, KLF10, PAIP1, and RCN1 have not yet been studied in gliomas. Three mRNAs were identified as oncogenes in gliomas, which was consistent with our multivariate Cox regression analysis result: IGFBP5 can increase cell invasion and inhibit cell proliferation via the EMT and Akt signaling pathways in GBM ( Dong et al, 2020 ); IP6K2 was reported to promote cell proliferation and inhibit cell apoptosis under the regulation of the LINC00467/miR-339-3p axis ( Liang & Tang, 2020 ); and KPNA4 is capable of facilitating epithelial-mesenchymal transition in glioma, which can be suppressed by miR-181b, a tumor-suppressive miRNA ( Wang et al, 2015 ). Surprisingly, the roles of the other two mRNAs in glioma were shown to be different from our analysis result: NRP2 promoted glioma cell growth, invasion, and angiogenesis ( Zheng et al, 2013 ); and SEMA5A, whose expression is markedly reduced in higher grades of glioma, can impede motility and promote differentiation of human gliomas ( Li & Lee, 2010 ).…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, in gliomas, elevated levels of tissue IGFBP5 were associated with higher tumor grades and poor prognosis ( 36–38 ). Silencing IGFBP5 expression impedes invasion but promotes the proliferation of GBM cells in vitro , thus having opposing effects on two cellular hallmarks of neoplastic state ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP-5 is highly expressed in GBM, indeed its depletion results in an inhibition of cell invasion and concomitant increase in cell proliferation. The double role of IGFBP-5 is mechanistically associated with Akt and EMT signaling ( 60 ).…”
Section: The Igf Signaling Pathway In Gbmmentioning
confidence: 99%